Simulação hidrodinâmica bidimensional do banhado do Taim - Bulé, Bibiana Peruzzo (2020)
Wetlands are swampy ecosystems of great biodiversity, recognized as one of the most valuable natural resources in the world. The ecosystem focus of this study is the Taim Wetland (TW). Located in the southern portion of Rio Grande do Sul (Brazil) the place where TW is situated has large exploitation of areas for rice cultivation, which makes it necessary to withdraw massive volumes of water from its tributary, the Mangueira Lake. As a consequence, TW suffers from constant conflicts over the use of water in the region, since on one side there is local economic dependence on rice cultivation by the population and, on the other hand, conditions related to water availability are vital for maintaining the TW species and habitats. In addition to agriculture, the dynamics of TW are influenced directly by the neighboring systems, by structures inserted in the region and also by the climatic factors, which means that changes in climatic or regional components may be able to promote changes in TW. Since TW is a complex ecosystem of great importance to society which is suffering from management problems, there is a need to adjust a modern hydrological-hydrodynamic model that represents the phenomena that occur in the region, so that can be a better understanding of how external changes are able to lead to impacts in the water levels of TW and map floods and droughts conditions, serving as management and planning tools for these areas. In order to achieve the purpose of the study, the digital elevation model of the terrain was improved to include the relevant characteristics for flow propagation. Through satellite images, measurements in the field and information obtained from previous studies, it was possible to improve the general characterization of the terrain by inserting features such as roads, drainage channels and performing interventions for modeling the hydraulic structures. Based on the terrain information, hydrological data and important information of the study area, the model was set up to represent the dynamics of the TW using HEC-RAS 5.0.7, a free software, constantly updated. Thus, the calibrated model provides, among other information, the TW water level as a function of the variability in the water levels of Mangueira Lake and other input data, such as local precipitation and evaporation. In addition, the model represents physical characteristics of TW, such as the topographic information and the presence of macrophytes that influence the dynamics, so the result is faithful to the processes that influence its dynamics. The results of calibration and validation of this model were classified as “very good” and “good” according to the evaluation methodology adopted (NSE 0.90 and 0.79, PBIAS of -1.7% and 5.4% and RSR of 0.32 and 0.46). Through the result, there is a spatialized water layer for all periods of the simulation, hydrographs in the hydraulic structures, speed information at all points of the simulation, demonstration of the flow direction in the entire system and the possibility to create different simulation scenarios.